Analysis of dynamics of automobile cranes with the account of the rope elasticity - Di, Phan Nguyen; Gay, Bui Khac (Vietnam Journal of Mechanics, 1998)
Up to now, there is still a little of attention paid on the dynamical analysis of automobile crane system and only simple dynamical models are used for the related studies. In this paper, a relatively comprehensive model describing the dynamics of automobile crane with only the body lifting mechanism taken into account is presented. The numerical solution has been derived, illustrated by graphics and assessed.